PI3K p110β subunit in leptin receptor expressing cells is required for the acute hypophagia induced by endotoxemia - Beatriz C. Borges; David Garcia-Galiano; Rodrigo Rorato; Lucila L.K. Elias; Carol F. Elias (Elsevier, 2016)
Objective: Hypophagia and increased energy expenditure under inflammatory conditions, such as that observed after bacterial lipopolysaccharide (LPS) administration, are associated with leptin secretion. The hypophagic effect of leptin depends in part on the activation of PI3K signaling pathway. However, the role of PI3K in the endotoxemia-induced hypophagia has not been determined. Methods: In an attempt to examine the functional contribution of the PI3K pathway in hypophagia and weight loss induced by LPS (100 ug/Kg, ip), we performed a central pharmacological PI3K inhibition (LY294002). Additionally, to gain mechanistic insights on the role of the catalytic PI3K p110α subunit in leptin responsive cells, mice expressing Cre-recombinase driven by the Lepr promoter (LepR-Cre) were crossed with mice carrying a loxP-modified p110α allele (Pi3kca gene) (LepRΔp110α). As studies have suggested that the PI3K p110β subunit has a dominant role over p110α in energy homeostasis, we further crossed LepR-Cre mice with loxP-modified p110α and p110β (Pi3kcb gene) alleles (LepRΔp110α+β). In order to verify the requirement of leptin in PI3K effects on food intake, we also used leptin-deficient ob/ob mice. Results: We found that LPS stimulates PI3K and STAT3 signaling pathways in cells expressing the leptin receptor. Central PI3K inhibition prevented LPS-induced hypophagia and weight loss. Genetic deletion of p110α subunit selectively in LepR cells had no effect on LPS-induced hypophagia and weight loss. However, p110α and p110β double deletion in LepR cells prevented LPS-induced hypophagia and partially reversed the weight loss. Leptin deficiency blunted LPS-induced acute pAKT and pSTAT3 phosphorylation and the acute suppression of food intake. Conclusions: Our studies show that the PI3K p110β subunit in LepR cells is required for acute endotoxemic hypophagia. The data provide promising approaches for PI3K inhibition in preventing low energy balance and cachectic states during inflammatory challenges. Keywords: LPS, Metabolism, Leptin, Hypothalamus, Inflammation